2020
DOI: 10.1017/s104795112000102x
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter radiofrequency ablation using near-zero fluoroscopy in children with fascicular ventricular tachycardia: a single-centre experience

Abstract: Objective:Fascicular tachycardia is a common form of sustained idiopathic left ventricular tachycardia. This study aimed to achieve successful results with catheter ablation procedures performed through three-dimensional electroanatomic mapping using near-zero fluoroscopy in fascicular tachycardia patients.Methods and results:In this study, we included 33 consecutive children with fascicular tachycardia, for whom we performed a transcatheter radiofrequency ablation procedure using the EnSite® system. Activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A recurrence rate of 20% and 3% was recorded during short-and long-term follow-ups. Repeat ablations achieved permanent success in all cases 24,25 . Only the last four cases were performed in our series with 3-D mapping after introducing this technology in our center.…”
Section: Interventional Treatmentmentioning
confidence: 83%
See 2 more Smart Citations
“…A recurrence rate of 20% and 3% was recorded during short-and long-term follow-ups. Repeat ablations achieved permanent success in all cases 24,25 . Only the last four cases were performed in our series with 3-D mapping after introducing this technology in our center.…”
Section: Interventional Treatmentmentioning
confidence: 83%
“…In a small series of four patients with a mean age of 14.5 years (4-20 years), success was achieved in all cases using noncontact mapping (EnSite ArrayTM) 23 . Two recent studies with EnSite NavXTM totaling 53 children reported an acute success rate of 95% and 100%, with a median fluoroscopy time between 1.25 and 5.1 minutes 24,25 , although fluoroscopy was not used in 91% of cases 23 .…”
Section: Interventional Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The major concern in catheter ablation in pediatric patients is procedural safety [ 7 ]. Several reports have confirmed the safety of VT catheter ablation in the pediatric population [ [8] , [9] , [10] , [11] ]. Most reports include idiopathic VT and common reentrant fascicular forms.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, the zero-fluoroscopy group had no radiation exposure during the entire ablation procedure or any loss of procedural efficacy or safety. Zero-fluoroscopy RFCA can completely avoid fluoroscopy exposure during ablation, thereby reducing the risk of malignancy in children (36,37). With the development of technology, people have an increasing need to lead a healthy life.…”
Section: Discussionmentioning
confidence: 99%